Effect of remimazolam on postoperative delirium and cognitive function in adults undergoing general anesthesia or procedural sedation: a meta-analysis of randomized controlled trials - Ji-In Park; Hyo-Seok Na; Ji-Na Kim; Jung-Hee Ryu; Howon Jang; Hyun-Jung Shin (Korean Journal of Anesthesiology)
Background Remimazolam is a novel short-acting benzodiazepine. This study compared the effects of remimazolam and propofol on cognitive function in adult patients after surgery or other procedures. Methods We searched electronic databases, including PubMed, Embase, CENTRAL, Web of Science, and Scopus, for relevant studies. The primary outcome was the proportion of participants who experienced delirium or impaired cognitive function postoperatively. Secondary outcomes included the incidence of hypotension, bradycardia, and postoperative nausea and vomiting. We estimated the odds ratios (OR) and mean differences (MD) with 95% CIs using a random-effects model. Results In total, 1295 patients from 11 randomized controlled trials were included. The incidence of postoperative delirium was 8.0% in the remimazolam group and 10.4% in the propofol group that was not significantly different (OR: 0.74, 95% CI [0.39–1.42], P = 0.369, I2 = 32%). More favorable cognitive function, as assessed using the Mini-Mental State Examination, was observed in the remimazolam group compared to the propofol group (MD: 1.06, 95% CI [0.32–1.80], P = 0.005, I2 = 89%). Remimazolam lowered the incidence of hypotension (OR: 0.28, 95% CI [0.21–0.37], P = 0.000, I2 = 0%) compared to propofol. Conclusions Remimazolam did not increase the risk of postoperative delirium and maintained cognitive function well, providing hemodynamic stability during surgery compared to propofol.